Suicide-related disclosure: implications for inclusion and recovery. Issue 3 (24th June 2019) - Sheehan, Lindsay; Oexle, Nathalie; Bushman, Michael; Fulginiti, Anthony; Frey, Laura M.
Abstract : Purpose: People who have lived experiences with suicide often struggle with concealable stigmatized identities that threaten their inclusion and recovery. While disclosure of a stigmatized identity can promote support and recovery and therefore prevent suicide, it may also present distinct risks. The purpose of this paper is to summarize key issues in suicide-related disclosure, suggest theoretical models for describing suicide-related disclosure and identify research needs. Design/methodology/approach: This conceptual paper discusses the existing literature on disclosure of concealable stigmatized identities, then explores research on disclosure of suicidal ideation, suicide attempt and suicide loss. Theoretical models (disclosure processes model and interpersonal theory of suicide) that can be employed in understanding suicide-related disclosure are explored. Finally, the paper suggests areas for future research, including longitudinal research to identify strategic disclosure practices that can lead to greater inclusion and recovery. Findings: Research on suicide-related disclosure should differentiate between disclosure of past and current suicidality, incorporate theoretical frameworks and examine approaches for preparing potential confidants and disclosers for the disclosure process. Originality/value: This paper highlights issues unique to the disclosure of suicidal thoughts and behaviors, and to suicide loss.